The Experiences of University Students who Stutter: A Quantitative and Qualitative Study. (30th June 2015) - Meredith, G.; Packman, A.
Abstract: Traversing the undulating experience of a university degree can be an emotional journey for many students. But imagine the same journey for a student who has to contend with the uncertainty that a stutter gives to the ability to effectively communicate. There has been little research focus on the school experiences of children and teenagers who stutter, but there has been even less on the experiences of university students who stutter. The aim of this study wasto give a voice to people who stutter who have engaged with the Australian Higher Education system so that their experiences and views can be shared. It is hoped that this study will (1)prompt university students who stutter to be more proactive in accessing and asking for assistance when required and (2) educate university staff about how to better facilitate learning for these students. During 2009 a 58 question online survey was made available to Australian people who stutter aged 18 or older who had enrolled in a university degree course within the past 10 years. The survey was advertised via Australian stuttering-related Facebook groups, online stuttering forums and to eligible members of both the Australian Speak Easy Association and the McGuire Programme (Australia). Overall 102 full and valid responses were recorded during a five month period. The questions used were a mixture of scaled, open and closed ended types. Results were analysed using descriptive statistics and thematic analysis. Initially from a surface level view of the results of this study were encouraging and also surprising. Stuttering had only influenced 14 of the 102 surveyed students in terms of their degree choices and many of these choices prepared them for roles requiring strong communication skills. Amongst all the respondents only one had dropped out of university up to that point in time because of stuttering-related problems and of the 90 who had successfully graduated only 11 of them had admitted that stuttering was an influence on their post-graduate career choice. But once the data was investigated more thoroughly it was found that underneath all the academic success were stories of dissatisfaction and lost opportunities in terms of social interactions, academic engagement and at times also grade results. Some students had purposefully underperformed and avoided communicating with university teachers and peers in order to avoid the stress of stuttering. Also very few students had accessed any disability support service that their university had on offer. Those students who had accessed support services found the experience to be confusing, with many different steps and lack of flexibility. This study indicates that Australian universities need to be better informed about stuttering and more flexible in terms of offering support for students who stutter. However, students also need to be better informed in terms of the benefits of accessing support provision. There is a need to further explore the reasons and repercussions of student interactions with universities in order to fully educate all parties involved and enable a more constructive educational experience for tertiary students who stutter.